THE FLAVOUR OF COMMUNICATION (BALEAP Journal of Research and Practice, 2025)
The flavour of communication is a reflective narrative that recounts a journey of discovery using adapted CEFR (2020) mediation skills to develop more effective communication skills for a university pluricultural cohort of healthcare students. In mediation, language is conceptualised as more than a linguistic construct, as the skills focus primarily on the needs of the other person in the interaction. Is my message clear, am I intelligible? Can using soft skills such as respect and empathy render the interaction more successful, particularly if the other person should be from a different culture. The CEFR (2020) mediation skills tend to reflect various sociocultural and interactional competence theories (Vygotsky, 1978; Hymes, 1972; Canale & Swain, 1980; Kramsch, 1986) where the emphasis is getting communication right in the context. In CEFR (2020) mediation, with its unique and useful interplay of micro skills, all forms of communication are activated to facilitate understanding (Piccardo, 2020), as can and should happen in real-life. Mediation skills are transferrable academically and professionally. They can be used for a range of communicative acts and can make us more aware of the complex nature of language, which includes collective, cognitive and social functions (Piccardo et al., 2019).